Improvement of Erosion -Corrosion Resistance of Tin-Bronze Alloy by Addition of Al and Al2O3 via Powder Technology (Journal of University of Babylon for Engineering Sciences, 2019)
The porous (tin-bronze) alloy has many engineering applications, especially in filtration systems, self-lubricating loading chairs and heat exchangers. Because of its unique mechanical and physical properties, it combines light weight, good durability with permeability, thermal and electrical conductivity. In the present study, samples of tin-bronze alloy with chemical composition (90 % Cu, 10 % Sn) have been prepared by using powder metallurgy,(35 wt. %) high purity (99.6 wt. %) NaCl powder was used as a pore-forming agent for the generation of pores, which was subsequently removed by dissolved with water at (100˚C) followed by ultrasonic cleaning (Ultrasonic cleaner device). Aluminum (3%) and alumina (3%,  5%, and 7%) were added to the base alloy to prepare composite samples in addition to the base alloy and study the effect of these additives on physical ,mechanical, corrosion, and erosion -corrosion properties.The powders were mixed for 5 hours and pressed under 40 MPa. Samples were sintered at(200˚C) for one hour and then the temperature was raised to  (600˚C) for period of (180 min)  with heating  rate (10 ˚C/min)  in a vacuum atmosphere (10-4 Torr) Then let it cool inside the furnace to room temperature while ensuring continued air discharge. The results showed that the sample of the addition of (3% Al and 7% Al2O3,) failed in the sintering process while the rest of the samples succeeded in sintering process under the same conditions. Several tests were carried out including:  microstructure test (light optical microscopy), scanning electron microscopy test (SEM), X-ray diffraction test (XRD), Energy dispersion spectrometer test (EDS), Vickers micro-hardness test ,porosity, density, corrosion behavior  (Tafel), and erosion corrosion test. The results of the SEM showed the presence of particle (Al2O3) in the matrix of the samples containing the addition of alumina particles. While the results of the X-ray diffraction examination showed that the prepared samples consist of two phases α (Cu, Sn) which represents the alloy matrix and the second phase (ε-Cu3Sn) as an intermetallic compound. The results of the density and porosity tests showed a decrease in the density value after the addition of aluminum and alumina. This decreasing increases with the increase of the percentage of the addition of alumina, while the porosity increases slightly with the increase of this addition. Through the test of micro- hardness, the results showed that the addition of alumina and aluminum led to an increase in the hardness value, where it was observed to increase the hardness value from (44.41) Hv of the alloy without addition to (83.30Hv) When the percentage of addition was (3% Al+5% Al2O3). In corrosion tests, the results of the electrochemical corrosion test (Tafel) in the solution (3.5% NaCl) significantly improved the corrosion resistance as the current density value decreased from (1.76112 μA / mm2) for base alloy to (0.00326 μA / mm2) for composite sample of (3%Al) and (5% Al2O3).  While in the erosion- corrosion test in (3.5% NaCl solution), the rate of erosion corrosion in alloy( 90% Cu- 10% Sn) was (11.5*10-4 g/hr) and   the rate of erosion corrosion for alloy with addition of (3%Al+5%Al2O3) was (5.8*10-4 g/hr) at steady state condition.”